NOTE ON THE SYSTEMATICS AND BIONOMICS OF CHANDA SPP. (CENTROPOMIDAE) - Gupta, S K (Indian Journal of Fisheries, 2011)
Enlargement in the ranges of variations in morphometric features ofClianda noma (Ham.) and Chanda ranga (Ham.) from Banda (U.P.) is recordedand compared with the earlier descriptions. In the present study 'noma' isretained under genus Chanda instead of HamUtonia, as proposed by Brunner(1954), on the basis of differences noticed in the key characters. Bionomicalnotes on the two species are also added.